THE SYNERGY OF PEER EDUCATION AND DIGITAL TECHNOLOGY IN STRENGTHENING THE IMPLEMENTATION OF SMOKE-FREE AREAS - Salsabila, Syefira; Suhadi, Suhadi; Nurmaladewi, Nurmaladewi; Rezal, Farit; Hikmawati, Zainab; Indriani, Della (LPPM Univ. Ibn Khaldun Bogor, 2025)
This program aims to strengthen the role of students as peer educators and to develop digital campaigns supporting the implementation of SFA within schools and at home. The activities began with initial coordination and a needs assessment conducted in collaboration with the principal and supervising teachers to map students’ readiness and interests. Based on the selection results, fifteen students were chosen as SFA Ambassadors. The subsequent stages included peer educator training, followed by the production of educational digital content, in which students created digital comics using the Canva application. The comics featured themes such as the dangers of smoking, peer influence, the benefits of healthy living, and the importance of SFA implementation in schools. These were then disseminated through digital campaigns and peer education activities. The program concluded with monitoring and evaluation, including surveys of students and parents, analysis of digital engagement, and reflections from the peer educators. The results of this community service activity successfully achieved its primary objectives, namely enhancing students’ capacity and role as agents of change in creating a smoke-free school environment. Through training, mentoring, and digital campaigns, students demonstrated improved understanding of the dangers of smoking, awareness of the importance of smoke-free policies, and developed communication and creative skills in delivering health messages to their peers and the surrounding community